General Beekeeping Structure in Sivas, Türkiye - Arslan, Erhan; Bayraktar, Metin (Ataturk Universitesi, 2023)
In this study, the level of beekeeping activities in Sivas, which has a wide area, and the technical, economic, and market possibilities of honey production and its by-products were evaluated. As well as, it is foreseen to be a source for studies on beekeeping. A survey was conducted in a total of 325 enterprises out of 2097 beekeeping enterprises existing in Sivas province center and in 16 districts. The data obtained were evaluated by considering appropriate statistical methods and the current situation, problems, and development opportunities of beekeeping in Sivas province were tried to be revealed. It has been observed that breeders have problems such as harsh and long winter conditions, wintering problems, shortage of quality and suitable queen bees, inability to find the market opportunity for the produced honey, and insufficient activities of the organizations. It has been concluded that increasing the number of hives through education, encourag-ing wandering, and producing mutual projects with government programs will increase honey production per hive. With the increase in honey production and the availability of suitable market conditions, the income of the rural people will increase as well as population migration will be prevented. © Author(s).
Arı Yetiştiriciliğinin Genel Yapısı Sivas, Türkiye
Keywords: Beekeeping; honey production; number of colonies; socioeconomic structure; Türkiye